Dependency Law, Coalitions of Actors and Welfare Regimes in Two Spanish Autonomous Regions: Andalusia and Aragon (2007-2017) - Del Campo, Esther; Sánchez Reinón, Manuel; López Sánchez, Eliseo (Política y Sociedad, 2018)
This article analyzes how the Dependency Law and the coalitions of actors that conformed to their promotion, development or veto, have modified the autonomous welfare regimes making, although they are familiaristic models, incorporate elements of hybridization of a more universalist character, which are the postulates of the same Law and the coalition promoting it at the state level. This is based on a theoretical framework based, on the one hand, on advocacy coalitions, and on the other, on welfare regimes. The empirical research is carried out in two Spanish autonomous communities, Andalusia and Aragon in the period 2007-2017.
Keywords: dependency; advocacy coalitions; welfare regimes; social policies; political decentralization; Spain